Analysis and Design of a Human Resources Performance Measurement System for the Nutmeg Oil Agro-industry in Aceh - Fadhil, Rahmat; Djatna, Taufik; Maarif, M. Syamsul (Journal of Regional and City Planning, 2017)
Abstract. This article aims to develop a model of human resources (HR) performance measurement for the nutmeg oil (Myristica fragrans) agro-industry in Aceh based on the Human Resource Scorecard (HRSC) method. The study uses the Relief method of system formulation to assess the effect of key performance attributes and to determine the association rules to facilitate the performance measurement system by taking into account the relationships between the attributes based on the support value and confidence value using Association Rules Mining (ARM). The analysis and design of the system are conducted using the System Development Life Cycle (SDLC) method that includes the analysis of system requirements, and Business Process Model and Notation (BPMN) using Sybase-Power Designer version 16.5. The results showed that the analysis system is successfully developed through describing in detail the process flow of the entire circuit system in the study. The Relief method for system design was capable of producing a rank system of key attributes in HR performance measurement, namely high-performance work system (HPWS) and human resource system alignment (HRSA). The advanced data handling process with ARM generated association rules with the three highest rankings of the overall HR performance measurement system.Keywords. Association rules mining, human resource scorecard, nutmeg oil, performance, relief.Abstrak. Artikel ini bertujuan untuk mengembangkan model sistem pengukuran kinerja sumber daya manusia (SDM) agroindustri minyak pala (Myristica fragrans) Aceh berdasarkan metode Human Resource Scorecard (HRSC). Formulasi sistem menggunakan metode Relief untuk mengetahui pengaruh kinerja utama dari suatu atribut yang dinilai dan menentukan aturan asosiasi untuk memudahkan pengukuran kinerja dengan memperhatikan hubungan antar atribut berdasarkan nilai penunjang dan nilai kepastian menggunakan metode Association Rules Mining (ARM). Analisis dan desain sistem dilakukan mengikuti metode System Development Life Cycle (SDLC) meliputi analisa kebutuhan sistem, use case diagram, dan Business Process Model and Notation (BPMN) dengan menggunakan software Sybase-PowerDesigner version 16.5. Hasil penelitian menunjukkan bahwa analisis sistem berhasil dikembangkan dengan menggambarkan aliran proses secara detail dari seluruh rangkaian sistem yang dikaji. Desain sistem melalui metode Relief mampu menghasilkan perangkingan atribut utama dalam pengukuran kinerja SDM, yaitu sistem kerja performansi tinggi (high performance work system/HPWS) dan keselarasan sistem SDM (human resource system alignment/HRSA). Proses penanganan data lanjutan dengan ARM diperoleh aturan asosiasi dengan tiga peringkat tertinggi yang dapat mewakili keseluruhan sistem pengukuran kinerja SDM. Kata kunci. association rules mining, human resource scorecard, kinerja, minyak pala, relief.